Activation of Autophagy Through the NLRP3/mTOR Pathway: A Potential Mechanism for Alleviation of Pneumonia by QingFei Yin - Sun, Xiaozhou; Wang, Dandan; Ding, Lizhong; Xu, Yan; Qi, Wenxiu; Zhao, Daqing; Liu, Li; Yin, Chengcheng; Cui, Changsheng; Wang, Zhongtian; Sun, Liwei; Sun, Liping (Frontiers in Pharmacology, 2022)
QingFei Yin (QFY), a Chinese traditional medicine recipe, is known for its excellent therapeutic pharmacological effects for the treatment of bacterial lung infections, although its molecular mechanism of action remains unknown. Here, QFY chemical composition was determined using a High-Performance Liquid Chromatography-Mass (HPLC-MS/MS)-based method then QFY was evaluated for protective pharmacological effects against pneumonia using two models: a Streptococcus pneumoniae-induced in vivo mouse model and an in vitro pneumolysin (PLY)-induced murine lung alveolar-derived MH-S cell line-based model. Notably, QFY exerted prominent anti-pneumonia effects both in vivo and in vitro. To further explore QFY protective effects, 4D label-free proteomics analysis, pathologic evaluation, and immunohistochemical (IHC) analysis were conducted to identify cellular pathways involved in QFY protection. Notably, our results indicated that NF-κB/NLRP3 and autophagy pathways may contribute to pharmacological effects associated with QFY-based protection. Briefly, QFY triggered autophagy via down-regulation of upstream NLRP3/mTOR signaling pathway events, resulting in the amelioration of inflammatory injury. Collectively, our results revealed molecular mechanisms underlying QFY protection against pneumonia as a foundation for the future development of novel treatments to combat this disease and reduce antibiotic abuse.